Penerapan Katekese Audio Visual Dalam Pengembangan Iman Umat Di Stasi St. Bonifasius Ombolata - Kristiana Mendrofa; Alexius Poto Obe; Wilman Berkat Jaya Hulu (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Application of Audio Visual Catechism to increase the enthusiasm of the people in catechesis activities. The problem in this study is how to apply audio-visual catechism in catechesis activities at St. Boniface Ombolata. The aim is to find out how audio-visual catechism is applied in catechesis activities at St. Boniface Ombolata. This research approach is descriptive qualitative. Data collection techniques by interview and observation. Data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions. In this study, researchers found that the application of audio-visual catechism in catechesis activities at St. Boniface Ombolata, can have a significant influence on the involvement and enthusiasm of the people, who are actively engaged in participating in various forms of catechism that are more useful and fun. Apart from that, it is also an effort to develop the faith of the people, to have creativity, initiative, and self-confidence in conveying the communication of faith for the life of the church.